2009
DOI: 10.1002/jmri.21678
|View full text |Cite
|
Sign up to set email alerts
|

Use of ultrasmall superparamagnetic particles of iron oxide (USPIO)‐enhanced MRI to demonstrate diffuse inflammation in the normal‐appearing white matter (NAWM) of multiple sclerosis (MS) patients: An exploratory study

Abstract: Purpose:To explore ultrasmall superparamagnetic particles of iron oxide (USPIO) as a marker for diffuse inflammation in multiple sclerosis (MS) normal-appearing white matter (NAWM), using quantitative MRI. Disease activity in the NAWM of MS patients partly explains why MRI lesion burden correlates only moderately with disability. USPIO have been shown to visualize the cellular component of inflammation in focal MS lesions. In this study, we aimed to explore USPIO as a marker for the more diffuse inflammation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 34 publications
1
32
0
1
Order By: Relevance
“…[27] Furthermore, global changes in the T1 signal in normal appearing brain tissue can demonstrate subtle generalized inflammatory activity without apparent BBB damage. [28] Clinical pilot trials have demonstrated that the use of both GBCA and USPIO in MS patients identifies more inflammatory lesions than gadolinium alone, range from a 4% to 244% increase. [27,29,30] The subgroup of lesions that enhanced with both contrast agents were characterized by a more severe evolution.…”
Section: Ultrasmall Superparamagnetic Particles Of Iron Oxidementioning
confidence: 99%
“…[27] Furthermore, global changes in the T1 signal in normal appearing brain tissue can demonstrate subtle generalized inflammatory activity without apparent BBB damage. [28] Clinical pilot trials have demonstrated that the use of both GBCA and USPIO in MS patients identifies more inflammatory lesions than gadolinium alone, range from a 4% to 244% increase. [27,29,30] The subgroup of lesions that enhanced with both contrast agents were characterized by a more severe evolution.…”
Section: Ultrasmall Superparamagnetic Particles Of Iron Oxidementioning
confidence: 99%
“…In addition, USPIO-enhanced MRI seems to be a new marker for diffuse inflammation in MS normalappearing white matter (Vellinga et al, 2009). Interestingly, three patterns of USPIO-enhancement have been observed, contrary to routine Gd-DTPA, showing that sensitivity and specificity of MRI in MS can be improved using USPIO.…”
Section: Perspectives In Advanced Magnetic Resonance Imaging Techniquesmentioning
confidence: 99%
“…Moreover, the same lesions can change their pattern of enhancement over time (Vellinga et al, 2008). Furthermore, USPIO-enhanced MRI may not only disclose a greater number of 'active' MS lesions but may also detect subtle and diffuse inflammatory activity in MS patients not visible on conventional T2-weighted MR sequences and unrelated to Gd-DTPA enhancement (Vellinga et al, 2009 …”
Section: New Mr Contrast Agentsmentioning
confidence: 99%